Pharmacist-Led Pediatric Diarrhea Management: A Systematic Review of Knowledge and Recommendation Appropriateness - Ebtavanny, Tamara Gusti; Fitri, Salsabilah Aida; Suhartono, Suhartono; Hariadini, Ayuk Lawuningtyas (Brawijaya University, 2025)
Diarrhea remains a leading cause of morbidity and mortality among children, particularly in areas with inadequate sanitation. Community pharmacists often serve as the first point of care, making their role crucial in ensuring appropriate, guideline-based management of pediatric diarrhea. This systematic review aimed to evaluate pharmacists’ knowledge and the appropriateness of their recommendations for treating pediatric diarrhea. A systematic literature review was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Searches were performed via Harzing’s Publish or Perish on Google Scholar, PubMed, and Crossref using keywords: